2021
DOI: 10.1186/s12875-020-01359-8
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour among general practitioners: a systematic review

Abstract: Background Sedentary behaviour is when someone is awake, in a sitting, lying or reclining posture and is an independent risk factor for multiple causes of morbidity and mortality. A dose-response relationship has been demonstrated, whereby increasing sedentary time corresponds with increasing mortality rate. This study aimed to identify current levels of sedentary behaviour among General Practitioners (GPs), by examining and synthesising how sedentary behaviour has been measured in the primary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
6
0
4
Order By: Relevance
“…Primarily during this COVID-19 pandemic, most of them work from home, with an average daily working time for sedentary jobs of 7.21±3.23 hours/day. The results of this study are consistent with the other researchers who revealed that the majority of time spent by workers is sitting [43]- [45]. During the Covid-19 pandemic, employees who worked from home spent more time engaging in sedentary behavior [29].…”
Section: Discussionsupporting
confidence: 92%
“…Primarily during this COVID-19 pandemic, most of them work from home, with an average daily working time for sedentary jobs of 7.21±3.23 hours/day. The results of this study are consistent with the other researchers who revealed that the majority of time spent by workers is sitting [43]- [45]. During the Covid-19 pandemic, employees who worked from home spent more time engaging in sedentary behavior [29].…”
Section: Discussionsupporting
confidence: 92%
“…Los más sedentarios fueron los de especialidad quirúrgica, probablemente debido a su doble turno laboral y es más frecuente en el sexo femenino. En otros estudios realizados en médicos de países de la región (Argentina, Colombia, Chile) y de otros continentes (Camerún, Irlanda y Estonia) encontraron también predominio de la conducta (5,6,13,14,(17)(18)(19)(20) sedentaria como FRCV . La conducta sedentaria es un factor de riesgo modificable, por lo…”
Section: Discussionunclassified
“…Se encontró una frecuencia baja de la DM2 con relación a otros FRCV, con predominio absoluto del sexo masculino, probablemente este hallazgo sea debido a que esta enfermedad se presenta en edades más avanzadas. En otros estudios en médicos con edad mayor a esta población encontraron (14)(15)(16)(17)19,29) mayor frecuencia de DM2 .…”
Section: Discussionunclassified
“…O CS se refere ao tempo em vigília que o indivíduo passa deitado, sentado ou reclinado com baixo gasto energético, ou seja, abaixo de 1,5 equivalentes metabólicos. 14,15 Sugere-se que esse comportamento é prejudicial à saúde cardiorrespiratória, metabólica e musculoesquelética, 13,16,17 portanto, poderia associar-se à incapacidade funcional. 14,[18][19][20] Em estudo realizado nos Estados Unidos, verificou-se que as chances de incapacidade se mostraram mais elevadas (OR: 1,14; IC 95%: 1,02; 1,29) em idosas com mais de 85 anos que permaneciam sentadas por 10 horas diárias, quando comparadas às idosas que ficavam tempos inferiores a 5 horas diárias em CS.…”
Section: Introductionunclassified